Medial Patellofemoral Ligament Reconstruction and Nonanatomic Stabilization Techniques in Skeletally Immature Patients - Pilone, Carola; Bonasia, Davide Edoardo; Rosso, Federica; Cottino, Umberto; Mazzola, Claudio; Blonna, Davide; Rossi, Roberto; Sigascot Knee Committee (Joints, 2019)
Patellar instability is a common cause of knee disability in children and adolescent, with a high recurrence rate. When conservative treatment fails, surgical options should be considered. The femoral insertion of the medial patellofemoral ligament (MPFL) is in close proximity to the distal femoral growth plate and precautions should be taken to avoid injuries to the physis. Anatomical features of the MPFL complex, with focus on the relationship between femoral MPFL attachment and femoral physis, are discussed together with surgical tips to avoid injuries to the growth plates. The aim of this article is to review the recent literature regarding MPFL reconstruction and other stabilization techniques for patellofemoral instability in skeletally immature patients, focusing on the different surgical options available. These can be classified as anatomical versus nonanatomical, proximal versus distal realignments, or based on the graft used: free graft and pedicled graft (quadriceps, patellar tendon, hamstring, and adductor magnus).
Keywords: medial patellofemoral ligament; children; adolescent; MPFL; patellar instability